The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fneur.2022.997913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive peripheral magnetic stimulation on spasticity evaluated with modified Ashworth scale/Ashworth scale in patients with spastic paralysis: A systematic review and meta-analysis

Abstract: BackgroundSpasticity is a common motor disorder resulting from upper motor neuron lesions. It has a serious influence on an individual's motor function and daily activity. Repetitive peripheral magnetic stimulation (rPMS) is a non-invasive and painless approach developed for therapeutic intervention in clinical rehabilitation. However, the effectiveness of this intervention on spasticity in patients with spastic paralysis remains uncertain.ObjectiveThis study aimed to investigate the effectiveness of rPMS on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…The potential mechanism may involve the neuromodulation effect of rPMS when applied to muscles or nerves. Pan et al, 2022 [ 17 ], conducted a systematic review of eight randomized controlled trials (RCTs) and a meta-analysis of six trials involving 170 patients with chronic stroke (>6 months). When evaluated with the AS or MAS, the results indicated that rPMS has the potential to reduce spasticity in the upper and lower extremities.…”
Section: Resultsmentioning
confidence: 99%
“…The potential mechanism may involve the neuromodulation effect of rPMS when applied to muscles or nerves. Pan et al, 2022 [ 17 ], conducted a systematic review of eight randomized controlled trials (RCTs) and a meta-analysis of six trials involving 170 patients with chronic stroke (>6 months). When evaluated with the AS or MAS, the results indicated that rPMS has the potential to reduce spasticity in the upper and lower extremities.…”
Section: Resultsmentioning
confidence: 99%
“…According to a systematic review and meta-analysis by Pan et al in 2022 ( 10 ) of eight randomized controlled trials (RCTs) involving 170 patients with chronic stroke, repetitive peripheral magnetic stimulation (rPMS) showed potential for reducing spasticity in both the upper and lower extremities.…”
Section: Rpms For Muscle Spasticity and Sensitization Theorymentioning
confidence: 99%
“…The exact mechanism by which rPMS decreases spasticity is not fully understood, but it is believed to involve a combination of increased somatosensory and proprioceptive input, cortical activation, and tissue softening effects ( 10 , 36 , 37 ). Studies have shown that sensory deficits are associated with the development of spasticity, and rPMS may help increase somatosensory and proprioceptive afferents.…”
Section: Rpms For Muscle Spasticity and Sensitization Theorymentioning
confidence: 99%
See 2 more Smart Citations